The knowledge preservation problem in the nuclear industry and the role of Web-based tools in its solution. Issue 5 (October 2019) - Geraskin, N.I.; Kulikov, E.G.; Glebov, V.B.
This case study analyses an application of distance training in the practice of nuclear knowledge preservation. The purpose of the research is to evaluate the potential of distance training in solving the problem of knowledge preservation in the nuclear industry. Thirty specialists from different European countries participated in the pilot training experiments. It was found that the efficacy of distance training depends directly on the convenience and ease of the knowledge transmission process, the possibility for the trainees to combine training with their professional activities, the ability to work independently and a conscious desire on the part of trainees to improve their professional competencies. The study included a comprehensive evaluation of the distance training platform Cyber Learning Platform for Network Education and Training (CLP4NET) in the context of nuclear knowledge preservation. It was found that CLP4NET provided a friendly interface, was relatively easy to use and allowed an extensive application of interactive data representation forms and ample communication between training participants.